O problemie skuteczności polityki fiskalnej i pieniężnej - Krawczyk, Marcin (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The article reviews theoretical analyses of effectiveness of fiscal and monetary policies. The first part concentrates on classical and new classical arguments on ineffectiveness of fiscal and monetary stimulus, i.e. proving that the stimulus does not influence real economic aggregates. These arguments include laissez-fairedoctrine and rational expectations, aggregate supply, and continuous market clearing hypotheses. The second part contains detailed description of adjustment processes brought about by fiscal and monetary expansions considered by contemporary theorists (e.g. D. Elmendorf and G. N. Mankiw) as “conventional macroeconomics”. These processes serve as theoretical argument in favor of a monetary accommodation of fiscal expansion. The third part forms a concise review of macroeconomic concepts which show that conventional adjustment process can be interrupted or even stopped during any of their phases (ricardian equivalencetheorem, Friedman's money illusion liquidity trap, investment insensitivity, Tobin's crowding out effect). In the final part, the author points out that monetary accommodation can weaken effectiveness of fiscal expansion.